Neutrophil gelatinase associated lipocalin in predicting postoperative acute kidney injury in elderly - ORHON ERGÜN, MELİHA; ZENGİN, SENİYYE ÜLGEN; UMUROĞLU, TÜMAY (SPRINGER LONDON LTD, 2022)
Background Elderly patients are at increased risk of developing acute kidney injury (AKI) following major surgery and rapid diagnosis is essential. Aim This study aimed to examine the potential utility of plasma neutrophil gelatinase associated lipocalin levels in early prediction of AKI in geriatric patients undergoing laparotomic oncological surgery. Methods This prospective single-center cohort study included 60 geriatric patients (>= 65 years of age) that underwent major oncologic surgery with laparotomy. Perioperative measurements of plasma creatinine, blood urinary nitrogen, plasma lactate, urine output, and neutrophil gelatinase associated lipocalin (NGAL) were made. Patients were followed for AKI development, which is the primary outcome measure, and predictive role of NGAL was investigated. Results At 48 h follow-up, AKI developed in 13 patients (21.7%). Significant differences in creatinine (p < 0.001), NGAL (p < 0.001), and urine output levels (p = 0.001) were evident over time between the two groups. High NGAL measurements at 6 and 24 h after surgery seem to be highly predictive of AKI development. At 6 h, a plasma NGAL level greater than 71.8 ng/mL has a sensitivity and specificity of 85% and 81% in predicting subsequent AKI development. Conclusions Plasma NGAL levels seem to represent an early and reliable marker for AKI in elderly patients undergoing laparotomic surgery with the potential to allow early diagnosis and prevent further renal deterioration. Further confirmatory studies are warranted. Trial registration The study was registered to ClinicalTrials.gov (number, NCT05030727). Implication statement Elderly patients are at increased risk of postoperative acute kidney injury (AKI). This study shows that plasma neutrophil gelatinase associated lipocalin is a helpful marker to predict AKI in elderly patients undergoing laparotomic major surgery, which will allow early diagnosis and prevent further renal deterioration in this vulnerable patient group.
Keywords: Abdominal surgery; Acute kidney injury (AKI); Elderly; Laparotomy; Oncologic surgery; Plasma neutrophil gelatinase associated lipocalin (pNGAL); CARDIOPULMONARY BYPASS; CYSTATIN C; BIOMARKER; OUTCOMES